A szegénység társadalmi meghatározói a posztkommunista társadalmakban - Domański, Henryk; Bíró, Dávid; Hegedűs, Rita (Szociológiai Szemle, 2024)
The purpose of this analysis is to shed light on distribution of poverty within the social structure. Using comparable national survey data from Bulgaria, Poland, Romania, Russia, Slovakia, and Hungary we determine to what extent social determinants of poverty observed in the capitalist West are also at work in the specific context of East European societies. Second area of inquiry, here, concerns the formation of the underclass. In searching for a post-communist underclass this analysis attempts to figure out the social location of the poor relative to positions occupied by intelligentsia, other non-manual categories, working class, peasants, and owners. The distinctive characteristics of the Western underclass are labor market detachment, social isolation, and material deprivation. Using discrimination analysis we examine the placement of the poor within the social structure relative to occupationally based class categories. This analysis shows that in multidimensional space as defined in terms of social origin, educational achievements, housing conditions, material possessions, and ethnicity there is no significant differences between the poor and occupationally-based class categories in Bulgaria, Hungary, and Poland. Contrariwise, significant distinctions of this kind appear in Romania, Slovakia, and Russia. In interpretation of these findings we seek to answer the question whether after decade of political and economic transformations, unique features of poverty in Eastern Europe tend to intermingle with universal patterns.